Community dental clinics: providers' perspectives. Issue 3 (15th October 2012) - Wallace, Bruce B.; MacEntee, Michael I.; Harrison, Rosamund; Hole, Rachelle; Mitton, Craig
Abstract Objectives Not‐for‐profit community dental clinics attempt to address the inequities of oral health care for disadvantaged communities, but there is little information about how they operate. The objective of this article is to explain from the perspective of senior staff how five community dental clinics in British Columbia, Canada, provide services. Methods The mixed‐methods case study included the five not‐for‐profit dental clinics with full‐time staff who provided a wide range of dental services. We conducted open‐ended interviews to saturation with eight senior administrative staff selected purposefully because of their comprehensive knowledge of the development and operation of the clinics and supplemented their information with a year's aggregated data on patients, treatments, and operating costs. Results The interview participants described the benefits of integrating dentistry with other health and social services usually within community health centres, although they doubted the sustainability of the clinics without reliable financial support from public funds. Aggregated data showed that 75% of the patients had either publically funded or no coverage for dental services, while the others had employer‐sponsored dental insurance. Financial subsidies from regional health authorities allowed two of the clinics to treat only patients who are economically vulnerable and provide all services at reduced costs. Clinics without government subsidies used the fees paid by some patients to subsidize treatment for others who could not afford treatment. Conclusions Not‐for‐profit dental clinics provide dental services beyond pain relief for underserved communities. Dental services are integrated with other health and community services and located in accessible locations. However, all of the participants expressed concerns about the sustainability of the clinics without reliable public revenues.